How do you factor 12+ 16x - 3x ^ { 2}?

2 Answers
Jun 15, 2017

=(6-x)(2+3x)

Explanation:

12+16x-3x^2

=12-2x+18x-3x^2

=2(6-x)+3x(6-x)

=(6-x)(2+3x)

Jun 15, 2017

The equation can be factorised to (-3x - 2)(x - 6)

Explanation:

Use the general formula
x = (-b +- sqrt(b^2 -4ac))/(2a)

Substitute in the given values
x = (-16 +- sqrt(16^2 -4*-3*12))/(-6)

simplify
x = (-16 +- 20)/(-6)

x_"1" = 6
x_"2" = -2/3

Put those values back into a(x-x_"1")(x-x_"2")

gives

-3(x + 2/3)(x - 6)

rearranging
(-3x - 2)(x - 6)